Reforma al artículo 309 del código orgánico integral penal por la falta de tipificación de distintas formas de usura a través de instrumentos mercantiles y societarios - Costa Cevallos, Marcelo Armando (2015)
Usury is directly related to the active operations that are generated by the disposal of the Financial Institutions Act through the national financial system and are known as loans or through mutual loans referring the Ecuadorian Civil Code; these operations must pursue an active rate is regulated by the Central Bank of Ecuador and the Banking Board. In summary Usury an unlawful action by the usurer person or entity requires a high interest financial performance for the money that has been given to the creditor. This criminal act is considered as an instant offense process, as it runs with the sole imposition of the advantages of the usurer, who duly warned by his victim, known in advance the precarious economy, acting and knowing that advantage behavior due to abusive and immoral use. The purpose of this investigation lies in determining a loophole from the issuance of the new Penal Code Integral (COIP), where, in its Article 309 criminalizes not usury properly, which would, in certain circumstances , constitute the crime and to transgress the rules without the criminal law provides for it, so a reform that article is absolutely necessary.